2021
DOI: 10.1016/j.clnesp.2021.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Precision of Lunar Dual-energy X-ray Absorptiometry (iDXA) in measuring body composition among colorectal cancer patients and healthy subjects

Abstract: Background & aims: High quality and precise methods are needed when monitoring changes in body composition among colorectal cancer (CRC) patients and healthy subjects. The aim of this study was to estimate precision of the Dual-energy X-ray absorptiometry (Lunar iDXA, GE Healthcare software enCORE version 16) in measuring body composition in CRC patients and healthy subjects. Methods: Precision error of iDXA in measuring body composition was investigated in the current study. Thirty CRC patients and 30 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
6
2
0
Order By: Relevance
“…In the absence of other works evaluating the precision of the Stratos DR, we could only compare our results to those previously obtained for other manufacturers. Nevertheless, our findings seem to be in accordance with the precision reported for the Lunar iDXA (ranging from 0.4% to 1%) (Henriksen et al, 2021; Hind et al, 2011; Rothney et al, 2012; Watson et al, 2017) and better than that of older generation DXA models such as Prodigy (ranging from 0.8% to 2.5%) (Oldroyd et al, 2003). It has also been suggested that the population studied and, particularly, an increase in body size can alter the precision of the measurement (Barlow et al, 2015; Hind et al, 2011; Knapp et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the absence of other works evaluating the precision of the Stratos DR, we could only compare our results to those previously obtained for other manufacturers. Nevertheless, our findings seem to be in accordance with the precision reported for the Lunar iDXA (ranging from 0.4% to 1%) (Henriksen et al, 2021; Hind et al, 2011; Rothney et al, 2012; Watson et al, 2017) and better than that of older generation DXA models such as Prodigy (ranging from 0.8% to 2.5%) (Oldroyd et al, 2003). It has also been suggested that the population studied and, particularly, an increase in body size can alter the precision of the measurement (Barlow et al, 2015; Hind et al, 2011; Knapp et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…The ISCD recommends that the minimum acceptable precision error within a population of interest should not exceed 3% for WB FM and 2% for WB FFST (Shuhart et al, 2019), which was the case in our study (<1.4%). These results indicated the good precision of the Stratos DR. We note than FFST showed a lower precision error compared to FM, which has previously been reported (Barlow et al, 2015; Bazzocchi et al, 2016; Henriksen et al, 2021; Rothney et al, 2012). In the absence of other works evaluating the precision of the Stratos DR, we could only compare our results to those previously obtained for other manufacturers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We additionally report the LSC (2.2%–4.9%) for our cohort, an essential metric for the correct interpretation of change in skeletal muscle over time and response to interventions. In the absence of standardized precision error reporting for L3 CT cross‐sectional skeletal muscle, we note that our values are comparable to the precision error (0.3%–2.0%) and LSC (1.4%–4.5%) reported for assessments of lean mass using DEXA 36,41–44 . Additionally, the cross‐sectional skeletal muscle measurements completed by our cohort of RDs are comparable to those completed by radiologists as reported by Perthen et al 45 In their study, radiologists ( N = 3) performed CT L3 skeletal muscle measurements in duplicate ( N = 29 images) using Hermes software 45 .…”
Section: Discussionsupporting
confidence: 83%
“…and LSC (1.4%-4.5%) reported for assessments of lean mass using DEXA. 36,[41][42][43][44] Additionally, the cross-sectional skeletal muscle measurements completed by our cohort of RDs are comparable to those completed by radiologists as reported by Perthen et al 45 In their study, radiologists (N = 3) performed CT L3 skeletal muscle measurements in duplicate (N = 29 images) using Hermes software. 45 Although they used different software and did not complete a precision assessment as we did here, radiologists' intraobserver and interobserver variabilities (1.57-2.89 cm…”
Section: Discussionsupporting
confidence: 83%